1975
DOI: 10.1139/f75-061
|View full text |Cite
|
Sign up to set email alerts
|

Population Estimate of the Humpback Whale (Megaptera novaeangliae) in the West Indies by Visual and Acoustic Techniques

Abstract: Visual track census and a new method, acoustic counting, were used to estimate the humpback whale (Megaptera novaeangliae) population in the West Indies. Results produced by the two methods differed to some extent. The average or best estimate was 1018 whales with a range of 785–1157. Silver and Navidad banks, containing approximately 85% of the total population, are presently the major nursery grounds in the West Indies. The humpback whale population in the western North Atlantic has increased since the early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 0 publications
2
45
0
Order By: Relevance
“…While most individuals maintain a neritic distribution in waters < 200 m in depth, mother-calf pairs prefer shallower waters close to shore (Félix & Haase 2005, Flórez-González et al 2007, Rasmussen et al 2007), similar to that found in other breeding areas (e.g. Dawbin 1966, Winn et al 1975, Glockner & Venus 1983, Smultea 1994, Ersts & Rosenbaum 2003, Morete et al 2007. It is unclear, however, what social and environmental conditions motivate the segregation of females and calves within the shallowest zones of their winter distribution, but it may be in response to ecological and social pressures such as predation risk (Chittleborough 1953, Herman & Antinoja 1977, harassment by males (Chittleborough 1958, Smultea 1994, Craig et al 2002, Cartwright & Sullivan 2009 and energy conservation (Whitehead & Moore 1982, Elwen & Best 2004.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…While most individuals maintain a neritic distribution in waters < 200 m in depth, mother-calf pairs prefer shallower waters close to shore (Félix & Haase 2005, Flórez-González et al 2007, Rasmussen et al 2007), similar to that found in other breeding areas (e.g. Dawbin 1966, Winn et al 1975, Glockner & Venus 1983, Smultea 1994, Ersts & Rosenbaum 2003, Morete et al 2007. It is unclear, however, what social and environmental conditions motivate the segregation of females and calves within the shallowest zones of their winter distribution, but it may be in response to ecological and social pressures such as predation risk (Chittleborough 1953, Herman & Antinoja 1977, harassment by males (Chittleborough 1958, Smultea 1994, Craig et al 2002, Cartwright & Sullivan 2009 and energy conservation (Whitehead & Moore 1982, Elwen & Best 2004.…”
Section: Introductionmentioning
confidence: 61%
“…In contrast to the Hawaiian Islands archipelago, where mother-calf pairs enter into deeper waters when moving widely between islands (Cerchio et al 1998, Darling 2001, in the southeast Pacific femalecalf pairs can move continuously along continental shallow zones. Conversely, in the Caribbean, the breeding population is concentrated in 2 shallow areas, the Silver and Navidad banks (Winn et al 1975), and in Brazil in the Abrolhos Archipelago where the maximum water depth is 20 m (Morete et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, acoustic techniques can augment visual surveys by providing methods for detection and identification of cetaceans when they are likely to be missed by visual observers. The use of acoustic techniques to complement visual efforts has increased rates and distances of detection for several cetacean species, including: humpback whales (Megaptera novaeangliae, Winn et al 1975), sperm whales (Physeter macrocephalus, Leaper et al 1992), blue and fin whales (Balaenoptera mzlsculus and B. physalus, Clark and Fristrup 1997), bowhead whales (Balaena mysticetus, Clark and Ellison 2OOO), striped dolphins (Stenella coeruleoalba, Gordon et al 2000), and other delphinids (Thomas et al 1986). While the use of acoustic techniques to detect marine mammals is becoming an increasingly common element of shipboard surveys, acoustic species identification has, until recently, received less attention (Steiner 1981, Potter et al 1994, Schultz and Corkeron 1994, Wang et al 1995, Mellinger and Clark 2000.…”
mentioning
confidence: 99%
“…During winter, most of the North Atlantic population is believed to migrate south to calving grounds in the West Indies (Winn et al, 1975;Whitehead and Moore, 1982;Stevick et al, 1998;Smith et al, 1999). Most humpbacks are found in this region from January through March, with some animals arriving as early as November and a few remaining in the area until June (Erdman et al, 1973;Winn et al, 1975; Katona and Beard, 1991;Reeves et al, 2001).…”
Section: Humpback Whale Megaptera Novaeangliaementioning
confidence: 99%
“…During winter, most of the North Atlantic population is believed to migrate south to calving grounds in the West Indies (Winn et al, 1975;Whitehead and Moore, 1982;Stevick et al, 1998;Smith et al, 1999). Most humpbacks are found in this region from January through March, with some animals arriving as early as November and a few remaining in the area until June (Erdman et al, 1973;Winn et al, 1975; Katona and Beard, 1991;Reeves et al, 2001). Humpback whales in the northeastern Caribbean Sea are primarily found off the northern coast of the Dominican Republic on Silver and Navidad Banks (Winn et al, 1975; Mattila et al, 1989) and in Samana Bay (Mattila et al, 1994), as well as on the Virgin and Anguilla Banks of the eastern Leeward Islands (Mattila and Clapham, 1989) and in the Mona Passage off western Puerto Rico (Mignucci-Giannoni, 1998;Sanders et al, 2005).…”
mentioning
confidence: 99%